(untitled) (Caderno de Pesquisa, 2014)
This study aimed to assess the relationships between abiotic variables and structure of epiphytic algae that colonize the 6th petiole macrophyte Eichhornia azurea (Sw.) Kunth, in three coastal lakes of Rio Grande do Sul, Brazil. We considered the density and composition algae and its relationship with the abiotic variables temperature, pH, alkalinity, conductivity, turbidity, dissolved oxygen, total nitrogen, nitrates, nitrites, ammonia, orthophosphate, total phosphorus and fecal coliforms. Samples were taken monthly from November/95 to May /96 up along a gradient of dilution and self-purification of pollution from the shallow Marcelino Lake dump that receives wastewater from the city of Osorio. The quantitative analysis of epiphyton identified 66 species of algae at the genus level, specific and infra-specific. The most representative classes were Bacillariophyceae, Cyanophyceae and Chlorophyceae. There was no influence of environmental variables on the epiphytic community, mainly on the class group of algae, as evidenced in the study of community structure. The cluster analysis with the densities of species of epiphytic algae revealed that the spatial distribution was more significant than the temporal variation. According to PCA there was a gradient showing the clearance of the degree of pollution of the lake in order to Marcelino and Peixoto and Pinguela with respect to the measured abiotic data. Finally, considering the biotic and abiotic measures, the main change in the race study followed the temporal variation of spatial variation.